2018
DOI: 10.1016/j.combustflame.2017.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Autoignition of straight-run naphtha: A promising fuel for advanced compression ignition engines

Abstract: CitationAlabbad M, Issayev G, Badra J, Voice AK, Giri BR, et al. (2018) Autoignition of straight-run naphtha: A promising fuel for advanced compression ignition engines. Combustion and Flame 189: 337-346. Available: http://dx. AbstractNaphtha, a low-octane distillate fuel, has been proposed as a promising low-cost fuel for advanced compression ignition engine technologies. Experimental and modelling studies have been conducted in this work to assess autoignition characteristics of naphtha for use in advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
6
29
0
Order By: Relevance
“…Detailed comparison of these fuels is available in It may be concluded from the experimental data of the GCI blend and the two surrogates that a multi-component surrogate with non-paraffinic content is needed to match the reactivity at low temperatures where PRF surrogate tends to be too reactive. Similar findings have recently been reported for two low-octane fuels [27,28]. It was also shown that these discrepancies in IDT at low temperatures can result in significant differences in the combustion phasing of a CI engine operating at low loads [28,34].…”
Section: Fig 1 Measured Ignition Delay Times Of the Gci Blend And Tsupporting
confidence: 71%
See 4 more Smart Citations
“…Detailed comparison of these fuels is available in It may be concluded from the experimental data of the GCI blend and the two surrogates that a multi-component surrogate with non-paraffinic content is needed to match the reactivity at low temperatures where PRF surrogate tends to be too reactive. Similar findings have recently been reported for two low-octane fuels [27,28]. It was also shown that these discrepancies in IDT at low temperatures can result in significant differences in the combustion phasing of a CI engine operating at low loads [28,34].…”
Section: Fig 1 Measured Ignition Delay Times Of the Gci Blend And Tsupporting
confidence: 71%
“…In addition, octane sensitivity (S = RON -MON) correlates quite well with the NTC behavior of the fuel [32,33]. We have shown previously that PRF, matching the RON of the real fuel, is a good surrogate for near-zero sensitivity fuels at high and intermediate temperatures [28,34,35]. However, the low-temperature reactivity is not strongly correlated to octane numbers but rather depends on the non-paraffinic components present in the real fuel [27,28,35,36].…”
Section: Fuel Characterization and Surrogate Formulationmentioning
confidence: 95%
See 3 more Smart Citations